2019
DOI: 10.1016/j.bbmt.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework and Key Research Questions in Educational Needs of Blood and Marrow Transplantation Patients, Caregivers, and Families

Abstract: Patient, caregiver, and family education and support was 1 of 6 key areas of interest identified by the National Marrow Donor Program/Be The Match 2-year project to prioritize patient-centered outcomes research (PCOR) goals for the blood and marrow transplantation (BMT) community. PCOR focuses on research to help patients and their caregivers make informed decisions about health care. Therefore, each area of interest was assigned to a working group with broad representation, including patients, caregivers, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
(113 reference statements)
0
9
0
Order By: Relevance
“…Successful education has been associated with decreased distress and increased patient satisfaction by better preparing patients for the transplantation process. Although to our knowledge not formally assessed in the current literature, regret among patients undergoing transplantation likely may stem from education that is not appropriately tailored to the cultural background, barriers to learning, and preferential learning styles of these individuals . Future research may use qualitative methods to better understand which type of regret is more prevalent among patients who have undergone transplantation and whether the regret is rooted in dissatisfaction with education, with consenting to transplantation, or something else.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful education has been associated with decreased distress and increased patient satisfaction by better preparing patients for the transplantation process. Although to our knowledge not formally assessed in the current literature, regret among patients undergoing transplantation likely may stem from education that is not appropriately tailored to the cultural background, barriers to learning, and preferential learning styles of these individuals . Future research may use qualitative methods to better understand which type of regret is more prevalent among patients who have undergone transplantation and whether the regret is rooted in dissatisfaction with education, with consenting to transplantation, or something else.…”
Section: Discussionmentioning
confidence: 99%
“…Although to our knowledge little research has been done to address regret after HCT, some research points to opportunities in the educational process as having significant potential to mitigate postdecisional regret. It is known that educational materials and delivery methods should be objective and accurate because patients undergoing transplantation tend to overestimate the benefits of BMT . Successful education has been associated with decreased distress and increased patient satisfaction by better preparing patients for the transplantation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More longterm education results might include improvement in survival and transplantation morbidity, accessibility of health care, willingness of patients / caregivers to return to work, and quality of life. 12,13 other study revealed that the preparation of family caregivers for their position must include clear education, including skills training. Preparing caregivers should be an ongoing process such that benefits are maintained and education programmes develop as required.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, the Health Care Management System offers some assistance to spouses who perform the function of caregivers. 5,13 With regard to time of treatment. In addition, there were statistically significant differences between the pre-and post-intervention programme, the current research in the same line of the previous study showed that full-time caregivers offer more support and can apply the information acquired by the caregiver from the programme.…”
Section: Concerning Caregivers' Demography Table (2)mentioning
confidence: 99%